2015
DOI: 10.1016/j.ceca.2015.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunctions during progression of dystrophic cardiomyopathy

Abstract: Duchenne muscular dystrophy (DMD) is a progressive muscle disease with severe cardiac complications. It is believed that cellular oxidative stress and augmented Ca 2+ signaling drives the development of cardiac pathology. Some mitochondrial and metabolic dysfunctions have also been reported. Here we investigate cellular mechanisms responsible for impaired mitochondrial metabolism in dystrophic cardiomyopathy at early stages of the disease. We employed electrophysiological and imaging techniques to study mitoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 35 publications
1
45
1
Order By: Relevance
“…These organelles generate ATP from metabolites through oxidative phosphorylation. Degradation in mitochondrial structure was correlated with substantial and persistent elevation in resting cytosolic sodium levels [33]. The LEXRF images show that sodium is more concentrated in the nucleus of the cardiomyocytes.…”
Section: Discussionmentioning
confidence: 91%
“…These organelles generate ATP from metabolites through oxidative phosphorylation. Degradation in mitochondrial structure was correlated with substantial and persistent elevation in resting cytosolic sodium levels [33]. The LEXRF images show that sodium is more concentrated in the nucleus of the cardiomyocytes.…”
Section: Discussionmentioning
confidence: 91%
“…Countless, studies showed the cardioprotective role of cyclosporine on the heart in different situation in coronary artery bypass graft (GABG) and ischemic-reperfusion injury(IRI [26].In the cardiac injury that occurred as a result of ischemia and myocardial infarction the mitochondria play an important role in the cardiac cell homeostasis and any mitochondrial dysfunction that occurred through opening of the mitochondrial permeability transition pore which considered as critical determinant of cardiomyocyte death in the heart [27].In addition, the use of cyclosporine to prevent mitochondrial permeability transition pore opening at the onset of reperfusion will limiting myocardial infarction size [28].Additionally, cardiotoxicity induced by doxorubicin lead to free radical production which will coalesce with membrane phospholipids and cause lipid peroxidation thus, increase in the MDA level causing cell damage and necrosis [29]. The mitochondrial dysfunction due to fatty acid oxidation may increase the ischemic damage which leads to cell depletion from high-energy phosphate due to mitochondrial enzyme dysfunction and subsequently the mitochondrial membrane was depolarized and mitochondrial membrane transition pores will be opened and the mitochondrial reactive oxygen species will increase and exacerbates the oxidative stress [30].Thus, the utilizing of cyclosporine will protects the heart from oxidative stress and will restoring the pore to the original state which has protective effect to cardiomyocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Overview Ventricular cardiomyocytes isolated from hearts of a mouse model of DMD (mdx mice) exhibit a number of distinct characteristics compared to cells from hearts of wild type (control group) animals: 1) their plasmalemmal membrane is more fragile [10,11]; 2) ionic fluxes across the membrane are increased [11,15]; 3) resting cytosolic Ca 2+ and Na + levels are elevated [11,15,16]; 4) intracellular Ca 2+ transients evoked by mechanical challenges are enhanced [10,17,18]; 5) excitation-contraction coupling (EC-coupling) is hypersensitive [19,20]; 6) the cytosolic compartment is severely oxidized due to enhanced activity of sarcolemmal NAD(P)H oxidase type II (NOX2) [16,21]; 7) mitochondrial redox state is shifted towards a more oxidative state [22]; and 8) mitochondria undergo irreversible depolarizations during increased workload due to enhanced opening of mitochondrial permeability transitions pore [16,22,23]. Moreover, damaged mitochondria are not efficiently removed from the hearts due to deficiency in the PINK1/PARKIN mitophagy pathway [24], eventually leading to the deficit in ATP supply.…”
Section: Search For Novel Pharmacological Targets: Cellular Manifestamentioning
confidence: 99%
“…This results in reverse operation of ATP-synthase to the point where it consumes ATP instead of producing it. This, in turn, facilitates cell death by apoptotic or necrotic mechanisms [22]. To make things worse, impaired mitochondrial autophagy has been recently demonstrated in DMD [24].…”
Section: Mitochondrial and Metabolic Dysfunctions In Dmdmentioning
confidence: 99%